Kitāb Bahasa Arab al-Madrasī Li aṣ-Ṣaff ar-Rābi` al-Ibtidā’ī Wa Taḥlīluhu Min Ḥaiṡ Tadarruj al-Mādah - Salvina Ulfa; Azwir Azwir (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2022)
In the teaching-learning process, there are several components interrelated each other. These components include: students, teachers, objectives, materials, methods, media and evaluation. The criteria for the content of textbooks that are suitable for using by education units have been determined by the BNSP as stated in the Regulation of the Education Minister and Culture of the Republic of Indonesia No. 8 of 2016 concerning books used in educational units article 3 paragraph 5 that the content of the textbook of lesson must cover aspects of material, linguistic, material presentation, and graphic. Besides these four aspects, teaching materials also need to be considered in a textbook. Teaching materials in textbooks are not only in accordance with the curriculum, but also they must be of high quality. William Francis Mackey explained that the aspects in seeing the quality of language teaching materials in a textbook, namely the aspects of selecting, gradation, presentation, and repetition. The researcher found that the subject matter for the fourth grade of the elementary school was not in the order and the grammar presented in the fourth grade of the elementary school was more than the grammar presented in the fifth Arabic for the elementary school. Therefore, the researcher analyzed the